β-Defensin 129 Attenuates Bacterial Endotoxin-Induced Inflammation and Intestinal Epithelial Cell Apoptosis - Xie, Kunhong; Xie, Hongmei; Su, Guoqi; Chen, Daiwen; Yu, Bing; Mao, Xiangbing; Huang, Zhiqing; Yu, Jie; Luo, Junqiu; Zheng, Ping; Luo, Yuheng; He, Jun (Frontiers in Immunology, 2019)
Abstract Defensins have attracted considerable research interest worldwide because of their potential to serve as a substitute for antibiotics. In this study, we characterized a novel porcine β-defensin (pBD129) and explored its role in alleviating bacterial endotoxin-induced inflammation and intestinal epithelium atrophy. The pBD129 gene was cloned and expressed in Escherichia coli. A recombinant pBD129 protein was also purified. To explore its role in alleviating the endotoxin-induced inflammation, mice with or without lipopolysaccharide (LPS) challenge were treated by the pBD129 at different doses. The recombinant pBD129 showed significant antimicrobial activities against the E. coli and Streptococcus with a minimal inhibitory concentration (MICs) of 32 μg/mL. Hemolytic assays showed that the pBD129 had no detrimental impact on cell viabilities. Interestingly, we found that pBD129 attenuated LPS-induced inflammatory responses by decreasing serum concentrations of inflammatory cytokines such as the IL-1β, IL-6, and TNF-α (P<0.05). Moreover, pBD129 elevated the intestinal villus height (P<0.05) and enhanced the expression and localization of the major tight junction-associated protein ZO-1 in LPS-challenged mice. Additionally, pDB129 at a high dose significantly decreased serum diamine oxidase (DAO) concentration (P<0.05) and reduced intestinal epithelium cell apoptosis (P<0.05) in LPS-challenged mice. Importantly, pBD129 elevated the expression level of Bcl-2-associated death promoter (Bcl-2), but down-regulated the expression levels of apoptosis-related genes such as the B-cell lymphoma-2-associated X protein (Bax), BH3-interacting domain death agonist (Bid), cysteinyl aspartate-specific proteinase-3 (Caspase-3), and caspase-9 in the intestinal mucosa (P<0.05). These results suggested a novel function of the mammalian defensins, and the anti-bacterial and anti-inflammatory properties of pBD129 may allow it a potential substitute for conventionally used antibiotics or drugs.